Theoretical Insights for Materials Properties of Cyclic Organic Nanorings. Issue 10 (3rd September 2020) - Pérez‐Jiménez, Ángel J.; Sancho‐García, Juan C.
Abstract: The synthesis of new carbon nanoforms with remarkable and fine‐tuned bulk properties still represents a formidable challenge, with cyclic organic nanorings emerging in recent years for the template‐driven design of this kind of systems. The design and engineering of these materials can be first controlled at the molecular scale, to further induce their specific self‐assembly toward tailored properties at the nanoscale. Theoretical studies have lately contributed to the understanding of the underlying physical effects, the development of synthetic strategies, and the rationalization of novel materials properties, employing a variety of methods ranging from accurate calculations of isolated molecules to atomistic molecular dynamics simulations of a large sample of molecules in realistic conditions, which will be reviewed here with a focus on the transition from single‐molecule to supramolecular properties. Abstract : Cyclic organic nanorings are promising materials with envisioned outstanding nanotechnological applications. Here, it is summarized how modern theoretical methods can provide insights for materials design, as well as for the understanding of the underlying structure–property relationships.